Dynamics of laboratory markers of endothelial dysfunction in patients with psoriatic arthritis under the influence of the interleukin-17A inhibitor netakimab - A. V. Petrov; O. A. Pritulo; A. A. Petrov (Современная ревматология, 2024)
Objective: a comparative evaluation of the effect of the interleukin-17A inhibitor (iIL) netakimab (NTK) and methotrexate (MTX) on laboratory markers of endothelial dysfunction in patients with psoriatic arthritis (PsA) in comparison with the dynamics of clinical efficacy indicators during 6 months of therapy.Material and methods. We performed a dynamic observation of 66 patients with PsA who were prescribed MTX and NTK for the first time. Thirty of them (group 1) received MTX 15 mg/week in the form of subcutaneous (s/c) injections in combination with folic acid 5 mg/week orally; 36 patients (group 2) received NTK as s/c injections at a dose of 120 mg at weeks 0, 1 and 2, and then once every 2 weeks until week 14, from week 14 – once every 4 weeks. The control group consisted of 20 substantially healthy individuals without skin diseases, rheumatic immune-inflammatory diseases of the musculoskeletal system and clinically significant diseases of the cardiovascular system. The clinical data were analyzed before, 3 and 6 months after the start of treatment. In all patients, the concentration of vascular endothelial growth factor (VEGF), endothelin 1 (En-1) and nitric oxide (NO) was analyzed before the start of treatment and at the end of the third month of treatment.Results and discussion. The concentration of laboratory markers for endothelial dysfunction was increased in patients with PsA compared to the control group: the median value of VEGF was 19.8 [4.5; 49.4] and 5.2 [0.5; 9.8] pg/ml (p=0.004), En-1 – 286.4 [154; 439] and 96.5 [32; 188] pg/ml (p=0.002), NO – 4.3 [2.1; 12.5] and 2.2 [0.2; 5.0] pg/ml (p=0.02), respectively. By the end of the 3rd month of therapy, a decrease in the concentration of indicators of endothelial dysfunction was observed. The dynamics of VEGF and En-1 concentrations was more pronounced in patients receiving NTK during the first 3 months of treatment than in patients receiving MTX treatment. The median decrease in VEGF concentration was 10.2 [8.4; 13.7] and 7.0 [5.6; 11.7] pg/ml (p=0.043), in En-1 – 184.6 [167; 202] and 112.7 [97; 136] pg/ml (p=0.008), respectively. A more significant decrease in LEI, PASI and NAPSI was achieved when NTK was used for 3 and 6 months compared to MTX therapy.Conclusion. The work demonstrated the ability of NTK, iIL17A, to reduce the initially elevated levels of laboratory markers of endothelial dysfunction.